Profil Kompetensi Soft Skills Dalam MendukungKebutuhan Dunia Kerja Pada Mahasiswa ProgramStudi Pendidikan Akuntansi Angkatan 2013Universitas Muhammadiyah Surakarta - Kurniawan, Andi, Drs. Budi Sutrisno, M.Pd (2016)
This research aims to find out: the first soft skills competency profiles in support of the needs of the world of work. Both the relevance of the learning process by improving the soft skills to do on KKNI. This type of research is a qualitative approach to Ethnography. The object of the research was Muhammadiyah University of Surakarta and the world of work (SMK Negeri 9 Surakarta, PT Monex Investindo Futures). Results of the study suggested: first, found 8 aspects of soft skills on the needs of the world of work i.e. the critical thinking ability, ethics, motivation skills, time management, communication skills, leadership, creative, and career planning. Soft skills competencies profiles accounting education students host 2013 divided 4 criteria, namely public, student organization, part time, and entrepreneur. The constraints of the General student learning was lacking soft skills in leadership and communication skills. The constraints of the student organization and part time, less able to qualify in time. While the obstacle of college students entrepreneur entrepreneurship motivation control related. Second, the implementation of the process of learning status of accounting education is in compliance with the improvement of soft skills-based curriculum in relation to students KKNI with ketercapaian four parameters based on improved soft skills i.e. job skills, the coverage of Science (knowledge), methods and level of ability to apply scientific, managerial and capacity.